Effectiveness of Merdeka Curriculum Implementation in ‎Learning Practices at Madrasah Ibtidaiyah - Milda 'Aisyah Furi; Syafrilian Akemza; Rofiq Sholeh; Nur Hidayatus Sholihah; Wahidmurni; Samsul Susilawati (JPI: Jurnal Pustaka Indonesia, 2026)
This study aims to analyze the effectiveness of the implementation of the Merdeka Curriculum in learning practices at MI Miftahul Ulum Kanigoro Pagelaran, Malang Regency. This study employed a qualitative approach with a case study design. The research subjects consisted of the madrasah principal, classroom teachers, curriculum development team, and administrative staff. Data were collected through observation, interviews, and documentation studies. The data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results showed that the implementation of the Merdeka Curriculum at MI Miftahul Ulum Kanigoro has been relatively effective. This effectiveness is reflected in the participatory curriculum planning process, the implementation of student-centered learning, and the structured implementation of the Projek Penguatan Profil Pelajar Pancasila (P5), which contributes to developing students’ character and competencies. Supporting factors for the implementation include proactive leadership of the madrasah principal, a collaborative culture among teachers, and continuous training programs. Meanwhile, the identified inhibiting factors include the limited competence of some teachers in developing teaching modules and assessments, limited learning technology facilities, high administrative workloads, and limited human resources. Therefore, the implementation of the Merdeka Curriculum at MI Miftahul Ulum Kanigoro Pagelaran, Malang Regency, has shown positive results, although further strengthening is still needed in teacher competence and infrastructure support to achieve more optimal effectiveness.